Shut-Down of Type IX Protein Secretion Alters the Host Immune Response to Tannerella forsythia and Porphyromonas gingivalis - Braun, Matthias L.; Tomek, Markus B.; Grünwald-Gruber, Clemens; Nguyen, Phuong Q.; Bloch, Susanne; Potempa, Jan S.; Andrukhov, Oleh; Schäffer, Christina (Frontiers in Cellular and Infection Microbiology, 2022)
Tannerella forsythia and Porphyromonas gingivalis target distinct virulence factors bearing a structurally conserved C-terminal domain (CTD) to the type IX protein secretion system (T9SS). The T9SS comprises an outer membrane translocation complex which works in concert with a signal peptidase for CTD cleavage. Among prominent T9SS cargo linked to periodontal diseases are the TfsA and TfsB components of T. forsythia’s cell surface (S-) layer, the bacterium’s BspA surface antigen and a set of cysteine proteinases (gingipains) from P. gingivalis. To assess the overall role of the bacterial T9SS in the host response, human macrophages and human gingival fibroblasts were stimulated with T. forsythia and P. gingivalis wild-type bacteria and T9SS signal peptidase deficient mutants defective in protein secretion, respectively. The immunostimulatory potential of these bacteria was compared by analysing the mRNA expression levels of the pro-inflammatory mediators IL-6, IL-8, MCP-1 and TNF-alpha by qPCR and by measuring the production of the corresponding proteins by ELISA. Shot-gun proteomics analysis of T. forsythia and P. gingivalis outer membrane preparations confirmed that several important CTD-bearing virulence factors which interact with the human immune system were depleted from the signal peptidase mutants, supportive of effective T9SS shut-down. Three and, more profoundly, 16 hours post stimulation, the T. forsythia T9SS mutant induced significantly less production of cytokines and the chemokine in human cells compared to the corresponding parent strain, while the opposite was observed for the P. gingivalis T9SS mutant. Our data indicates that T9SS shut-down translates into an altered inflammatory response and pinpoints the T9SS as a potential target for novel anti-periodontitis agents.